From governmental accounting into national accounts: adjustments diversity and materiality with evidence from the Iberian countries central governments - Jesus, M.; Jorge, S. (Innovar: Revista de Ciencias Administrativas y Sociales, 2014)
In a context where Governments around the world acknowledge a need for more informative governmental financial reporting to improve financial sustainability, the European Council is proposing EU member-States to adopt IPSASs-based standards to all subsectors of the General Government Sector (GGS), which are recognised as also allowing improving government finance statistics reliability. Consequently, the Governmental Accounting (GA) role of running and reporting on Governments’ budgets for purposes of decision-making and accountability is changing to include being a part in the EU budgetary and monetary policy, namely within the Euro zone. Such being considered, this paper objective is twofold. First, it aims at starting a debate in the literature concerning the ability of GA as it is across Europe to meet the European System of National and Regional Accounts (ESA) requirements concerning GGS data. This assumes particular relevance in a context where the two systems have to coexist, but given that budgetary reporting (GA) is the main input to ESA reporting (NA), reconciliation between the two systems is required. The second objective is of a more technical nature, empirically demonstrating diversity and materiality of the main adjustments to be made when converting GGS data from GA into NA. This assessment of adjustments diversity and materiality is done by using evidence for Portugal and Spain, focusing on Central Government data for the period of 2006-2009 and measuring their quantitative impact on the public (budgetary) deficit. The paper concludes that GA systems as they are across EU do not meet ESA requirements, so further alignment is needed to reduce adjustments when translating data from GA into NA as much as possible. Additionally, from the Iberian countries cases, main findings show the adjustments from GA into NA, both for Portugal and Spain, present great diversity. As to materiality, their impact is higher in Spain, but still significant in Portugal. Therefore, both reliability and comparability of final budgetary balances reported by EU member-States within the Excessive Deficit Procedures (EDP) requirements may be questionable.